Lifestyle (sketches from the countryside) - Stoyanov, Nikolay (Bidon Films, 2004)
A portrait of a Bulgarian village and its inhabitants, mostly pensioners: their habbits, their home-made alcohol and stories from old times. The two Hungarians students in Bulgarian language visiting the village to gather some "local culture" are everyone's focus of attention and courtesy. They have to listen to all the incredible stories, stand on their feet when an old Soviet hymn is played, keep up the pace with the seasoned drinkers, revel at the village club with the youngsters and attend a gathering of the village women at the reading-club…